Food safety for the 21st century : managing HACCP and food safety throughout the global supply chain - Wallace, Carol A. [ (Carol Anne)]; Mortimore, Sara E.; Sperber, William H. (Ames, Iowa : Wiley-Blackwell, 2011)
* Provides a practical and up-to-date text covering the essentials of food safety management in the global supply chain, giving the reader the knowledge and skills that they need to design, implement and maintain a world-class food safety programme